Molecular and Morphological Evidence Challenges the Records of the Extant Liverwort Ptilidium pulcherrimum in Eocene Baltic Amber - Heinrichs, Jochen; Scheben, Armin; Lee, Gaik Ee; Váňa, Jiří; Schäfer-Verwimp, Alfons; Krings, Michael; Schmidt, Alexander R (PloS one, 2015)
Preservation of liverworts in amber, a fossilized tree resin, is often exquisite. Twenty-three fossil species of liverworts have been described to date from Eocene (35-50 Ma) Baltic amber. In addition, two inclusions have been assigned to the extant species Ptilidium pulcherrimum (Ptilidiales or Porellales). However, the presence of the boreal P. pulcherrimum in the subtropical or warm-temperate Baltic amber forest challenges the phytogeographical interpretation of the Eocene flora. A re-investigation of one of the fossils believed to be P. pulcherrimum reveals that this specimen in fact represents the first fossil evidence of the genus Tetralophozia, and thus is re-described here as Tetralophozia groehnii sp. nov. A second fossil initially assigned to P. pulcherrimum is apparently lost, and can be reassessed only based on the original description and illustrations. This fossil is morphologically similar to the extant North Pacific endemic Ptilidium californicum, rather than P. pulcherrimum. Divergence time estimates based on chloroplast DNA sequences provide evidence of a Miocene origin of P. pulcherrimum, and thus also argue against the presence of this taxon in the Eocene. Ptilidium californicum originated 25-43 Ma ago. As a result, we cannot rule out that the Eocene fossil belongs to P. californicum. Alternatively, the fossil might represent a stem lineage element of Ptilidium or an early crown group species with morphological similarities to P. californicum.
Keywords: Evolution, Molecular; molekulární evoluce; zkameněliny; Marchantiophyta; Amber; jantar; Hepatophyta; Fossils